2021
DOI: 10.3390/su132111919
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Polish Tourists Traveling for Leisure Purposes during the COVID-19 Pandemic

Abstract: The research presented in this paper examines the experiences of Poles traveling for leisure purposes in the summer season of 2020, taking into account the context of the COVID-19 pandemic. The study involved the analysis of source data, including statistical data, and a survey administered via the computer-assisted web interviewing (CAWI) method. The survey questionnaire was created on the Google platform. The link to the questionnaire was provided via social media to participants of travel groups in the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…These findings are consistent with prior scholarly works and find resonance in existing literature (e.g. Abou-Shouk et al, 2022;Balińska and Olejniczak, 2021;Chandraet al, 2022;Hiamey et al, 2021;Pendergast, 2021;Selim et al, 2020) In contrast, this study provides empirical support for the impact of the quality of healthcare services on perceived travel risk. Travelers tend to perceive destinations equipped with robust healthcare systems as comparatively safer, a sentiment corroborated by the works of Akhavan et al (2023) and Barlan & Borbon (2022).…”
Section: Findings and Conclusionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with prior scholarly works and find resonance in existing literature (e.g. Abou-Shouk et al, 2022;Balińska and Olejniczak, 2021;Chandraet al, 2022;Hiamey et al, 2021;Pendergast, 2021;Selim et al, 2020) In contrast, this study provides empirical support for the impact of the quality of healthcare services on perceived travel risk. Travelers tend to perceive destinations equipped with robust healthcare systems as comparatively safer, a sentiment corroborated by the works of Akhavan et al (2023) and Barlan & Borbon (2022).…”
Section: Findings and Conclusionsupporting
confidence: 91%
“…Furthermore, other variables could be mediating or moderating the association between healthcare services and travel risk (Gorsuch, 1983;Hayes, 2018). For instance, it is plausible that the impact of HS on TR is more pronounced for travelers who exhibit heightened health and safety concerns (Balińska and Olejniczak, 2021). Moreover, the influence of HS on TR could be more pronounced in developed countries, where hygiene and safety standards are typically more stringent than in developing nations (Dwipayanti et al, 2021) The third hypothesis (H3) proposed a negative relationship between health care services (HC) and perceived travel risk (TR).…”
Section: Hypothesis Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified a research gap on this subject in the region of Central and Eastern Europe, where Poland is the largest country. So far, many works from China and Asian countries have been published, as well as a few works about Poland [ 74 , 75 , 76 ]. Tourism-themed groups on Facebook were used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Gastronomic attractions are not able to attract as many tourists as they used to Ref. [ 37 ]. Durmaz [ 38 ] found that crowded social distances are the main reason for decreasing people's interest.…”
Section: Literature Reviewmentioning
confidence: 99%